The golden temple - Charman, Katrina; Tondora, Judit (New York, NY : Branches/Scholastic Inc., 2020)
Tag, Skyla, and Blaze are on a new quest to find Blaze's family, and Thorn's twin brother, Claw (who claims to be nothing like his evil brother), has offered to guide them to the mysterious Golden Temple where the firehawks were last seen; but the jungle is full of dangers and Tag is not sure they can trust Claw--and even if they find the firehawks, will that help them return to their home in Perodia?
610L
Decoding demand: 76 (high) Semantic demand: 93 (very high) Syntactic demand: 74 (high) Structure demand: 85 (very high)
Keywords: Owls -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Fantasy fiction; Action and adventure fiction